Intelligibility in Speech Disorders : Theory, Measurement and Management. - Kent, Raymond D. (Studies in speech pathology and clinical linguistics, 1992)
The papers in this volume, written by authors experienced in intelligibility issues in speech pathology and related fields, describe the basic dimensions by which speech intelligibility can and must be understood. The dimensions are auditory perceptual, linguistic, acoustic and physiologic. These, in turn, are applied to the fundamental problems of definition and theory, measurement and clinical management. Only relatively recently has there been significant progress in formal intelligibility assessment and few, if any books have been published on intelligibility concerns in speech pathology.